Laminate
The laminate, featuring a polymer coating layer on a paper base material, addresses the challenges of recycling and environmental impact while meeting multiple performance criteria for food packaging, including aroma retention, thereby enhancing the flavor experience of packaged food.
Patent Information
- Application Number
- JP2021194279
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-11-30
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-11-30
AI Technical Summary
Existing laminates used for food packaging, which include a polyethylene layer, are difficult to recycle and have environmental concerns, while also struggling to meet multiple performance requirements such as water resistance, oil resistance, seasoning resistance, blocking, microwave resistance, and heat sealing, as well as maintaining the aroma of food.
A laminate is developed with a coating layer on a paper base material, where the coating layer consists of a polymer made from an ethylenically unsaturated monomer, specifically an alkyl(meth)acrylate, with a glass transition temperature between -40 to 30°C and 40 to 140°C, and an acid value of 20 to 40 mgKOH/g, applied at a coating amount of 0.5 to 10 g/m², achieving excellent air shielding properties.
The laminate satisfies all the required performance criteria for food packaging, including water resistance, oil resistance, seasoning resistance, blocking, microwave resistance, and heat sealing, while also effectively retaining the aroma of food, thus enhancing the food's flavor experience.
Smart Images

Figure 0007669915000008 
Figure 0007669915000009 
Figure 0007669915000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate. [Background technology]
[0002] There are various methods for simply packaging food, one of which is to use a laminate containing paper. In this case, the laminate is used instead of a paper base material alone because a typical paper base material cannot prevent the penetration of water or oil, and the moisture or oil in the food will seep out of the package, staining the hands or reducing the strength of the package itself, so it is necessary to laminate a water-resistant or oil-resistant layer on the paper base material. Polyethylene is often used as this water-resistant or oil-resistant layer, and a laminate in which polyethylene is laminated on a paper base material has been widely used.
[0003] In recent years, paper recycling has been accelerating due to the global trend of reducing environmental impact. However, the laminate laminated with the above-mentioned polyethylene requires expensive capital investment to remove the polyethylene film layer in the paper recycling process, making it difficult to recycle and hindering the promotion of recycling. In this context, laminates in the form of a paper base material coated with a coating agent are being actively studied as laminates that are easier to recycle. Furthermore, there is a demand for such coating agents to be materials that have a low environmental impact, and for example, Patent Document 1 discloses a coating agent that does not contain styrene as a monomer component.
[0004] Incidentally, various functions are required for laminates in food packaging applications. In addition to water resistance and oil resistance to prevent the moisture and oil contained in food from penetrating as much as possible, seasonings such as ketchup and sauce, which contain multiple components such as moisture, oil, salt, acid, and amino acids, are more likely to penetrate than simple water or oil, so resistance to the penetration of these seasonings (hereinafter referred to as "seasoning resistance") is required. In addition, blocking resistance is required so that the laminates can be taken out one by one when packaging food after being stored in a stack, and heat sealability is required so that, depending on the contents, a part of the laminate can be heat-sealed to form a shape that makes it easy to wrap food. Furthermore, after packaging food and taking it home, the food may be heated in a microwave oven as it is to warm it up. Therefore, it is necessary that water and oil do not penetrate and food does not stick to the laminate (hereinafter such resistance is referred to as "microwave oven resistance") even if it is reheated in a microwave oven and exposed to oil or steam at high temperatures.
[0005] When using the above-mentioned coating agents with low environmental impact, it has been difficult to obtain a laminate that simultaneously satisfies all of these various performance requirements.
[0006] Furthermore, the inventors thought that by imparting a function of trapping the aroma of food in addition to these functions, the flavor of the food can be felt more strongly when eaten, and a high-added-value laminate can be provided. However, the idea of trapping the aroma of food in a laminate having a paper base material and maintaining its deliciousness for a long period of time has not been conceived, and it has been difficult to design a laminate with such a function. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2001-303475 A Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a laminate which satisfies all of the performance requirements required for food packaging applications, such as water resistance, oil resistance, seasoning resistance, blocking properties, microwave oven resistance, and heat sealability, and which also has excellent food aroma retention properties. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention relates to a paper substrate having a coating layer (L) on at least one side thereof, the coating layer (L) containing a polymer (A) made of an ethylenically unsaturated monomer (a), the polymer (A) having a glass transition temperature in the range of -40 to 30°C and 40 to 140°C, and an acid value of 20 to 40 mgKOH / g, and the coating weight of the coating layer (L) being 0.5 to 10 g / m 2 and the laminate has an air barrier property of 20 kPa or less.
[0010] The present invention relates to the above laminate, wherein the ethylenically unsaturated monomer (a) contains an alkyl (meth)acrylate (a-1) in which the alkyl group is a methyl group, an ethyl group or an alkyl group having 3 to 8 carbon atoms.
[0011] The present invention relates to the above laminate, wherein the ethylenically unsaturated monomer (a) contains 85 to 97 mass% of alkyl (meth)acrylate (a-1-1) in which the alkyl group is a methyl group, an ethyl group or a linear alkyl group having 3 to 4 carbon atoms, based on the total mass of the ethylenically unsaturated monomer (a).
[0012] The laminate satisfies all the performance requirements for food packaging, such as water resistance, oil resistance, seasoning resistance, blocking properties, microwave resistance, and heat sealability, and is also excellent in air shielding. As a result of intensive research, the inventors have found that a laminate with excellent air shielding properties is also excellent in retaining the aroma of food. In other words, the laminate satisfies all the performance requirements for water resistance, oil resistance, seasoning resistance, blocking properties, microwave resistance, and heat sealability, and is also excellent in retaining the aroma of food. Effect of the Invention
[0013] The laminate of the present invention satisfies all of the performance requirements for food packaging applications, such as water resistance, oil resistance, seasoning resistance, blocking properties, microwave resistance, and heat sealability, and further provides a laminate that is excellent in retaining the aroma of food. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a front view of the air barrier property measuring device according to the present invention. [Diagram 2] FIG. 2 is a plan view of a glass filter in the air barrier property measuring device of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below. Needless to say, other embodiments are also included in the scope of the present invention as long as they are consistent with the gist of the present invention. In addition, in this specification, a numerical range specified using "~" includes the numerical values written before and after "~" as the range of the lower and upper limits. In addition, in this specification, "film" and "sheet" are not distinguished by thickness. In other words, in this specification, "sheet" includes thin film-like objects, and "film" includes thick sheet-like objects. Unless otherwise noted, the various components appearing in this specification may be used independently as a single type or as a combination of two or more types.
[0016] In this specification, unless otherwise specified, the terms "(meth)acrylic acid" and "(meth)acrylate" refer to "acrylic acid or methacrylic acid" and "acrylate or methacrylate", respectively. Furthermore, "(meth)acrylic acid ester monomer" is a general term for "acrylic acid ester monomer" and "methacrylic acid ester monomer". The monomer refers to an ethylenically unsaturated double bond-containing monomer.
[0017] <Laminate> The laminate of the present invention is formed by applying a coating liquid onto a paper substrate and drying the coating liquid to form a coating layer (L), and has a coating layer (L) on at least one side of the paper substrate. By forming such a laminate, it is possible to impart various properties to the paper substrate, such as water resistance, oil resistance, seasoning resistance, and blocking resistance. The laminate of the present application can be particularly suitably used for forming a sheet for packaging food (hereinafter, abbreviated as food packaging sheet), and can also be suitably used for applications in which the coating layer comes into direct contact with food.
[0018] <Paper base material> The paper base material is obtained by papermaking a paper material containing pulp, fillers, various auxiliaries, etc. That is, the paper support used in the present invention is not particularly limited, and examples thereof include bleached or unbleached kraft paper (acidic paper or neutral paper), fine paper, medium-quality paper, lightly coated paper, coated paper, paperboard, white paperboard, liner, semi-glassine paper, glassine paper, one-sided gloss paper, parchment paper, etc. Any type of paper that is commercially available for food packaging can be used. The basis weight of the paper base material is 5 to 100 g / m 2 is preferable, and 10 to 50 g / m 2 is preferable, and 15 to 30 g / m 2 By having the basis weight in this range, a uniform coating film without unevenness can be formed on the substrate, and the printing speed can be improved to increase productivity.
[0019] ≪Coating layer (L)≫ The coating layer (L) can be formed by applying a coating liquid containing a polymer (A) made of an ethylenically unsaturated monomer (a) onto a paper substrate and drying the coating liquid. The coating liquid may be water-based or solvent-based, but is preferably water-based from the viewpoints of environmental load and safety when in contact with food.
[0020] <Polymer (A) composed of ethylenically unsaturated monomer (a)> The polymer (A) (hereinafter, simply referred to as polymer (A)) made of the ethylenically unsaturated monomer (a) can be obtained by polymerizing the ethylenically unsaturated monomer (a) in water or a solvent using a radical polymerization initiator according to a conventional method. The polymerization method is not particularly limited, but it is preferable to use emulsion polymerization because it is easy to obtain a resin dispersion with a high molecular weight, low viscosity, and high solid content in an aqueous medium.
[0021] (Radical polymerization initiator) As the radical polymerization initiator used in the polymerization reaction of the ethylenically unsaturated monomer (a), a known oil-soluble polymerization initiator or water-soluble polymerization initiator can be used. These may be used alone or in combination of two or more kinds. The radical polymerization initiator is preferably used in an amount of 0.1 to 4 parts by mass, and more preferably 0.2 to 2 parts by mass, based on 100 parts by mass of the total amount of the ethylenically unsaturated monomer (a).
[0022] The oil-soluble polymerization initiator is not particularly limited, and examples thereof include organic peroxides such as benzoyl peroxide, tert-butyl peroxybenzoate, tert-butyl hydroperoxide, tert-butyl peroxy(2-ethylhexanoate), tert-butylperoxy-3,5,5-trimethylhexanoate, di-tert-butyl peroxide, and dilauroyl peroxide; azobis compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), and 1,1'-azobis-cyclohexane-1-carbonitrile; and the like.
[0023] In the emulsion polymerization, it is preferable to use a water-soluble polymerization initiator. As the water-soluble polymerization initiator, for example, conventionally known ones such as ammonium persulfate (APS), sodium persulfate (NPS), potassium persulfate (KPS), hydrogen peroxide, and 2,2'-azobis(2-methylpropionamidine) dihydrochloride can be suitably used.
[0024] (reducing agent) In emulsion polymerization, a reducing agent may be used in combination with the polymerization initiator. The use of a reducing agent in combination accelerates the emulsion polymerization rate and facilitates emulsion polymerization at low temperatures. Examples of the reducing agent include reducing organic compounds such as ascorbic acid, erythorbic acid, tartaric acid, citric acid, glucose, formaldehyde sulfoxylate, Rongalite, and metal salts of thiourea dioxide; and reducing inorganic compounds such as sodium thiosulfate, sodium sulfite, sodium bisulfite, sodium metabisulfite, and ferrous chloride. These reducing agents are preferably used in an amount of 0.05 to 5 parts by mass based on 100 parts by mass of the total amount of the ethylenically unsaturated monomer (a).
[0025] The polymerization temperature may be equal to or higher than the polymerization initiation temperature of the polymerization initiator, and is usually about 80° C. when a peroxide-based polymerization initiator is used. The polymerization time is not particularly limited, but is usually 2 to 24 hours. The ethylenically unsaturated monomer (a) may be polymerized by photochemical reaction or radiation exposure without using the above-mentioned polymerization initiator.
[0026] (Buffer or chain transfer agent) In the polymerization of the ethylenically unsaturated monomer (a), a buffer or a chain transfer agent may be further used as necessary. Examples of the buffer include sodium acetate, sodium citrate, and sodium bicarbonate. Examples of the chain transfer agent include n-hexyl mercaptan, n-heptyl mercaptan, t-hexyl mercaptan, t-heptyl mercaptan, n-octyl mercaptan, t-octyl mercaptan, n-nonyl mercaptan, t-nonyl mercaptan, n-decyl mercaptan, t-decyl mercaptan, n-undecyl mercaptan, t-undecyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, n-tridecyl mercaptan, t-tridecyl mercaptan, n-tetradecyl mercaptan, and t-tetradecyl mercaptan. mercaptan, n-heptadecyl mercaptan, t-heptadecyl mercaptan, t-hexadecyl mercaptan, n-hexadecyl mercaptan, n-heptadecyl mercaptan, n-octadecyl mercaptan, t-heptadecyl mercaptan, t-octadecyl mercaptan, mercaptan 2-ethylhexyl mercaptoacetate, octyl mercaptoacetate, methoxybutyl mercaptopropionate, 2-ethylhexyl mercaptopropionate, octyl mercaptopropionate, and stearyl mercaptopropionate. The buffer is preferably used in an amount of 0 to 1 part by mass, more preferably 0.05 to 0.5 parts by mass, based on 100 parts by mass of the total amount of the ethylenically unsaturated monomer (a). The chain transfer agent is preferably used in an amount of 0.4 to 3 parts by mass, more preferably 0.6 to 2 parts by mass, based on 100 parts by mass of the total amount of the ethylenically unsaturated monomer (a).
[0027] Among the above chain transfer agents, it is preferable to use a chain transfer agent represented by the following general formula (1).
[0028] [ka] R is a linear or branched alkyl group having 8 to 16 carbon atoms.
[0029] Examples of the chain transfer agent represented by general formula (2) include n-octyl mercaptan, t-octyl mercaptan, n-nonyl mercaptan, t-nonyl mercaptan, n-decyl mercaptan, t-decyl mercaptan, n-undecyl mercaptan, t-undecyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, n-tridecyl mercaptan, t-tridecyl mercaptan, n-tetradecyl mercaptan, t-tetradecyl mercaptan, n-heptadecyl mercaptan, t-heptadecyl mercaptan, t-hexadecyl mercaptan, and n-hexadecyl mercaptan.
[0030] The chain transfer agent is preferably used in the range of 0.4 to 3 parts by mass, more preferably 0.6 to 2 parts by mass, based on 100 parts by mass of the total amount of the ethylenically unsaturated monomer (a). By using it in the above range, the oil resistance of the coating layer (L) is further improved. It is believed that the chain transfer agent is incorporated into the terminal of the polymer (A) and contributes to the film-forming property of the resin, thereby improving the oil resistance. The introduction rate of the chain transfer agent of general formula (2) into the polymer is 100%.
[0031] (Basic compounds) In the polymerization of the ethylenically unsaturated monomer (a), a basic compound may be used as a neutralizing agent to enhance the stability of the polymer (A). Examples of the basic compound include ammonia water; various organic amines such as dimethylaminoethanol, diethanolamine, and triethanolamine; and inorganic alkali agents such as hydroxides of alkali metals such as sodium hydroxide, lithium hydroxide, and potassium hydroxide. Among these, ammonia water is preferred from the viewpoint of water resistance.
[0032] (Surfactant) In addition, when obtaining the polymer (A), a surfactant can be used. Examples of the surfactant include anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants, but from the viewpoint of safety and good coating film physical properties, anionic surfactants or nonionic surfactants are preferable. In addition, based on 100 parts by mass of the total amount of the ethylenically unsaturated monomer (a), the surfactant is preferably contained in the range of 0.1 to 2.0 parts by mass, more preferably 0.4 to 1.0 parts by mass. By being in these ranges, the water resistance of the coating film is further improved. It is considered that the surfactant contributes to the stability of the polymer (A) to assist film formation, and is not too compatible with water, making it difficult for swelling and dissolution to occur. The surfactant can be used alone or in combination with two or more kinds.
[0033] Examples of anionic surfactants that can be used include higher fatty acid salts such as sodium oleate, alkylarylsulfonates such as dodecylbenzenesulfonic acid, alkyl sulfates such as sodium lauryl sulfate, polyoxyethylene alkyl ether sulfates such as sodium polyoxyethylene lauryl ether sulfate, alkyl sulfosuccinates such as sodium monooctyl sulfosuccinate, sodium dioctyl sulfosuccinate, and sodium polyoxyethylene lauryl sulfosuccinate, and derivatives thereof, and polyoxyethylene distyrenated phenyl ether sulfate. However, from the viewpoint of being less likely to adversely affect the food resistance (seasoning resistance, microwave resistance) of the food packaging sheet, among the above, it is preferable that the surfactant is an alkyl sulfate or an alkyl sulfosuccinate, and more preferably that the alkyl sulfate is lauryl sulfate and the alkyl sulfosuccinate is dioctyl sulfosuccinate.
[0034] Examples of nonionic surfactants include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether and polyoxyethylene stearyl ether, polyoxyethylene alkyl phenyl ethers such as polyoxyethylene octyl phenyl ether and polyoxyethylene nonyl phenyl ether, sorbitan higher fatty acid esters such as sorbitan monolaurate, sorbitan monostearate, and sorbitan trioleate, polyoxyethylene sorbitan higher fatty acid esters such as polyoxyethylene sorbitan monolaurate and polyoxyethylene sorbitan monostearate, polyoxyethylene higher fatty acid esters such as polyoxyethylene monolaurate and polyoxyethylene monostearate, glycerin higher fatty acid esters such as oleic acid monoglyceride and stearic acid monoglyceride, polyoxyethylene-polyoxypropylene block copolymers, polyvinyl alcohol, polyvinylpyrrolidone, and polyoxyethylene distyrenated phenyl ether.
[0035] As the surfactant, a polymerizable surfactant having one or more radically polymerizable ethylenically unsaturated double bonds in the molecule can be used.
[0036] The polymerizable surfactant is preferably a polymerizable anionic surfactant or a polymerizable nonionic surfactant.
[0037] Examples of the polymerizable anionic surfactant include those having a main skeleton such as a sulfosuccinate ester, an alkyl ether, an alkyl phenyl ether, an alkyl phenyl ester, a (meth)acrylate sulfate ester, and a phosphate ester. Examples of the polymerizable nonionic surfactant include those having a main skeleton such as an alkyl ether, an alkyl phenyl ether, and an alkyl phenyl ester.
[0038] Among the above examples, the surfactant contains at least one of lauryl sulfate and diethylsulfosuccinate, and the surfactant contains preferably 0.1 to 2.0 parts by mass of both in total, and more preferably 0.4 to 1.0 part by mass, based on 100 parts by mass of the total amount of the ethylenically unsaturated monomer (a).
[0039] <Ethylenically unsaturated monomer (a)> Examples of the ethylenically unsaturated monomer (a) include alkyl (meth)acrylates (a-1) in which the alkyl group is a methyl group, an ethyl group, or an alkyl group having 3 to 8 carbon atoms, ethylenically unsaturated monomers (a-2) having a carboxy group, and other ethylenically unsaturated monomers (a-3) copolymerizable with the above (a-1) and (a-2). These monomers may be abbreviated as ethylenically unsaturated monomer (a-2) and ethylenically unsaturated monomer (a-3).
[0040] Examples of the alkyl (meth)acrylate (a-1) in which the alkyl group is a methyl group, an ethyl group, or an alkyl group having 3 to 8 carbon atoms include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, heptyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and octyl (meth)acrylate. Among these, alkyl (meth)acrylates (a-1-1) in which the alkyl group is a methyl group, an ethyl group, or a linear alkyl group having 3 to 4 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and n-butyl (meth)acrylate, are preferred. Furthermore, the polymer (A) preferably contains 85 to 97 mass % of alkyl (meth)acrylate (a-1-1) in which the alkyl group is a methyl group, an ethyl group, or a linear alkyl group having 3 to 4 carbon atoms, based on the total mass of the ethylenically unsaturated monomer (a), and more preferably contains 90 to 96 mass %. When the content of alkyl (meth)acrylate (a-1-1) in which the alkyl group is a methyl group, an ethyl group, or a linear alkyl group having 3 to 4 carbon atoms is within such a range, the dispersion stability of the resin fine particles during synthesis is significantly improved, resulting in a polymer (A) with excellent coatability and film-forming properties. The coating layer (L) formed by this polymer (A) can further improve the air shielding properties of the laminate due to its excellent coatability and film-forming properties.
[0041] Examples of the ethylenically unsaturated monomer (a-2) having a carboxyl group include acrylic acid, methacrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, citraconic acid, and cinnamic acid, but the ethylenically unsaturated monomer (a-2) having a carboxyl group preferably contains methacrylic acid, because the coating layer (L) has good coating film resistance against food-derived components. By containing methacrylic acid, the food resistance (seasoning resistance, microwave resistance) of the laminate is further improved.
[0042] The content of the ethylenically unsaturated monomer (a-2) having a carboxyl group is preferably 2 to 5 mass %, more preferably 4 to 4.9 mass %, based on the total mass of the ethylenically unsaturated monomer (a). By including the monomer in the above range, a food packaging sheet having excellent seasoning resistance, microwave resistance and heat sealability can be obtained.
[0043] The ethylenically unsaturated monomer (a-3) is an ethylenically unsaturated monomer other than the alkyl (meth)acrylate (a-1) in which the alkyl group is a methyl group, an ethyl group, or an alkyl group having 3 to 8 carbon atoms, and the ethylenically unsaturated monomer (a-2) having a carboxy group, which is copolymerizable with (a-1) and (a-2).
[0044] Examples of the other ethylenically unsaturated monomer (a-3) include aromatic ethylenically unsaturated monomers such as vinylnaphthalene, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxytetraethylene glycol (meth)acrylate, phenoxyhexaethylene glycol (meth)acrylate, phenoxyhexaethylene glycol (meth)acrylate, and phenyl (meth)acrylate; pentyl (meth)acrylate, heptyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, phenyl (meth)acrylate, and the like. ethylenically unsaturated monomers containing a straight or branched alkyl group having 5 or more carbon atoms, such as dipentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, and behenyl (meth)acrylate; ethylenically unsaturated monomers containing an alicyclic alkyl group, such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; ethylenically unsaturated monomers containing a fluorinated alkyl group, such as trifluoroethyl (meth)acrylate and heptadecafluorodecyl (meth)acrylate; ethylenically unsaturated monomers containing a sulfo group, such as sodium 2-acrylamido 2-methylpropanesulfonate, methallylsulfonic acid, methallylsulfonic acid, sodium methallylsulfonate, allylsulfonic acid, sodium allylsulfonate, ammonium allylsulfonate, and vinylsulfonic acid;(Meth)acrylamide, N-methoxymethyl-(meth)acrylamide, N-ethoxymethyl-(meth)acrylamide, N-propoxymethyl-(meth)acrylamide, N-butoxymethyl-(meth)acrylamide, N-pentoxymethyl-(meth)acrylamide, N,N-di(methoxymethyl)acrylamide, N-ethoxymethyl-N-methoxymethylmethacrylamide, N,N-di(ethoxymethyl)acrylamide, N-ethoxymethyl-N-propoxymethylmethacrylamide, N,N-di(propoxymethyl)acrylamide Amide group-containing ethylenically unsaturated acrylamide, such as N-butoxymethyl-N-(propoxymethyl)methacrylamide, N,N-di(butoxymethyl)acrylamide, N-butoxymethyl-N-(methoxymethyl)methacrylamide, N,N-di(pentoxymethyl)acrylamide, N-methoxymethyl-N-(pentoxymethyl)methacrylamide, N,N-dimethylaminopropylacrylamide, N,N-diethylaminopropylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, and diacetoneacrylamide. Monomers containing hydroxyl groups, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycerol mono(meth)acrylate, 4-hydroxyvinylbenzene, 1-ethynyl-1-cyclohexanol, and allyl alcohol; ethylenically unsaturated monomers containing polyoxyethylene groups, such as methoxypolyethylene glycol (meth)acrylate and polyethylene glycol (meth)acrylate; dimethylaminoethyl (meth)acrylate, diethyl aminoethyl (meth)acrylate, methylethylaminoethyl (meth)acrylate, etc., amino group-containing ethylenically unsaturated monomers such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methylethylaminoethyl (meth)acrylate, etc.; epoxy group-containing ethylenically unsaturated monomers such as glycidyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, etc.; ketone group-containing ethylenically unsaturated monomers such as diacetone (meth)acrylamide, acetoacetoxy (meth)acrylate, etc.;Allyl (meth)acrylate, 1-methylallyl (meth)acrylate, 2-methylallyl (meth)acrylate, 1-butenyl (meth)acrylate, 2-butenyl (meth)acrylate, 3-butenyl (meth)acrylate, 1,3-methyl-3-butenyl (meth)acrylate, 2-chloroallyl (meth)acrylate, 3-chloroallyl (meth)acrylate, o-allylphenyl (meth)acrylate, 2-(allyloxy)ethyl (meth)acrylate, allyl lactyl (meth)acrylate, citronellyl (meth)acrylate acrylate, geranyl (meth)acrylate, rosinyl (meth)acrylate, cinnamyl (meth)acrylate, diallyl maleate, diaryl itaconic acid, vinyl (meth)acrylate, vinyl crotonate, vinyl oleate, vinyl linoleate, 2-(2'-vinyloxyethoxy)ethyl (meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol (meth)acrylate, tetraethylene glycol (meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethylenically unsaturated monomers having two or more ethylenically unsaturated groups, such as meth)acrylate, 1,1,1-trishydroxymethylethane diacrylate, 1,1,1-trishydroxymethylethane triacrylate, 1,1,1-trishydroxymethylpropane triacrylate, divinylbenzene, divinyl adipate, diallyl isophthalate, diallyl phthalate, and diallyl maleate; γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxypropyltributoxy Alkoxysilyl group-containing ethylenically unsaturated monomers such as silane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-acryloxypropyltrimethoxysilane, γ-acryloxypropyltriethoxysilane, γ-acryloxypropylmethyldimethoxysilane, γ-methacryloxymethyltrimethoxysilane, γ-acryloxymethyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltributoxysilane, and vinylmethyldimethoxysilane;Methylol group-containing ethylenically unsaturated monomers such as N-methylol (meth)acrylamide, N,N-dimethylol (meth)acrylamide, and alkyl-etherified N-methylol (meth)acrylamide are included, but are not limited thereto. Among these, acrylamide, glycidyl methacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, or N-methylol acrylamide is more preferred.
[0045] In addition, styrenes such as styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, m-methylstyrene, dimethylaminostyrene, and diethylaminostyrene may be used to the extent that the effect is not impaired, but it is preferable not to include them from the viewpoint of environmental friendliness.
[0046] <Glass transition temperature> The polymer (A) has a glass transition temperature (hereinafter sometimes referred to as Tg) in the low temperature range of -40 to 30°C and in the high temperature range of 40 to 140°C. The polymer may also have a Tg outside these temperature ranges. When the low temperature Tg is in this range, the resistance to seasonings is particularly improved. This is thought to be because the inclusion of a flexible component in the polymer (A) forms a dense coating film, which can prevent the penetration of seasonings containing various components. On the other hand, when the high temperature Tg is in this range, the blocking resistance and microwave resistance are particularly improved. The lower temperature side Tg is more preferably in the range of -20 to 10°C, and the higher temperature side Tg is more preferably in the range of 70 to 140°C.
[0047] Examples of methods for preparing polymers (A) having different glass transition temperatures include multi-stage polymerization in which the monomer is dropped into the reaction system during emulsion polymerization in multiple stages, and the composition of the ethylenically unsaturated monomer is changed so that the Tg of the resulting polymer is different in each stage, and a method in which an acrylic resin is synthesized in advance by bulk polymerization or solution polymerization, dissolved or dispersed in an aqueous phase, and then an ethylenic monomer is dropped to polymerize so that a polymer having a Tg different from that of the previous acrylic resin is produced, etc. Among these, it is more preferable that the polymer (A) is synthesized by multi-stage polymerization, since the process is not complicated and the resulting polymer (A) has good dispersion stability.
[0048] The glass transition temperature in the present invention refers to the glass transition temperature measured by differential scanning calorimetry (DSC) for a resin obtained by drying the polymer (A) to a non-volatile content of 100% by mass. Details are described in the Examples section.
[0049] <Acid value> The acid value of the polymer (A) is in the range of 20 to 40 mgKOH / g, more preferably 30 to 40 mgKOH / g. When the acid value is in such a range, the interaction between the carboxy groups of the polymer (A) becomes strong, and the heat sealability is improved. The acid value of the polymer (A) was calculated from the value obtained by subjecting a pre-dried resin to potentiometric titration according to the method described in JIS K2501: 2003. Details are described in the Examples section.
[0050] <Optional ingredients> The coating agent for food packaging sheets of the present invention may contain additives such as wax, defoaming agent, extender pigment, leveling agent, preservative, etc. as optional components. It is preferable that the optional components do not have adverse effects on health if they remain in the laminate after coating. When a leveling agent or preservative is contained as an optional component, it is preferable that the leveling agent is contained in an amount of 0.1 to 5 parts by mass and the preservative is contained in an amount of 0.001 to 1 part by mass based on 100 parts by mass of the coating layer.
[0051] <Wax> The types of wax include paraffin wax, polyethylene wax, polypropylene wax, amide wax, ethylene / vinyl acetate copolymer wax, ethylene / acrylic acid copolymer wax, etc., with paraffin wax or polyethylene wax being preferred. Furthermore, these waxes are preferably used in an amount of 1 to 6 parts by mass based on 100 parts by mass of the coating layer. By being within these ranges, it is possible to improve water resistance in particular, and there is no adverse effect on other properties.
[0052] <Antifoaming agent> The types of antifoaming agents include mineral oil-based, polyether-based, fluorine-based, silicone-based, and acetylene glycol-based agents, with silicone-based agents being preferred. Silicone-based defoamers include, for example, oil-type, whose components are all silicone oil, oil compound-type, in which silica is added to silicone oil, emulsion-type, in which oil-type or oil compound-type defoamers are dispersed in water with a surfactant, powder (solid)-type, etc. Commercially available oil-type products include KF-96 and KF-6701 manufactured by Shin-Etsu Chemical Co., Ltd., DOWSIL SH200 manufactured by Dow Toray Co., Ltd., AIRASE5655 and TEGO Foamex840 manufactured by Evonik Industries, etc. Examples of oil compound types include KS-66 and KS-69 manufactured by Shin-Etsu Chemical Co., Ltd., DOWSIL ACP-3073, ACP-3258, and XIAMETER ACP-1500 manufactured by Dow-Toray Industries, Inc., and TEGO Foamex 810, TEGO Foamex 830, TEGO Foamex 832, TEGO Foamex 852, and TEGO Foamex 3062 manufactured by Evonik Industries. Examples of the emulsion type include KM-70, KM-71, KM-72, KM-75, and KM-85 manufactured by Shin-Etsu Chemical Co., Ltd., DOWSIL SM5571Emulsion, XIAMETER AFE-1520, and DOWSIL SH5507Emulsion manufactured by Dow Toray Co., Ltd., and TEGO Foamex815N, TEGO Foamex822, TEGO Foamex823, TEGO Foamex825, and TEGO Foamex1488 manufactured by Evonik Industries Co., Ltd. Among these, the oil type, oil compound type, and emulsion type defoamers thereof are preferred, and the oil compound type and emulsion type defoamers thereof are more preferred.
[0053] Originally, antifoaming agents are added to coating liquids to suppress bubbles in the coating liquid, and substances with low surface free energy are used. In this case, if the antifoaming agent used is appropriate, it is possible to suppress the generation of bubbles in the coating liquid during coating, which reduces coating film defects caused by these bubbles and improves air barrier properties. At the same time, it reduces coating film defects caused by repelling due to the low surface free energy of the antifoaming agent, and improves air barrier properties. The amount of the antifoaming agent in the coating layer (L) is preferably 0.005 to 1 part by mass, more preferably 0.075 to 0.5 parts by mass, and further preferably 0.01 to 0.3 parts by mass, based on 100 parts by mass of the coating layer.
[0054] The body pigment is preferably one approved as a food or food additive. Specific examples include talc, kaolin, bentonite, silica, calcium carbonate, barium sulfate, titanium oxide, diatomaceous earth (white carbon), cellulose powder, etc. When a body pigment is included as an optional component, it is preferable that the body pigment is contained in an amount of 1 to 50 parts by mass based on 100 parts by mass of the coating layer.
[0055] <Coating amount in laminate> The coating amount of the coating layer (L) in the laminate is the unit area (1 m) after drying. 2 In the present invention, the coating amount of the coating layer (L) is 0.5 to 10 g / m 2 and 1.0 to 8 g / m 2 More preferably, the thickness is 1.5 to 6 g / m 2 It is more preferable that the total coating amount is 0.5 g / m 2 If the total coating amount is 10g / m or more, the coating layer is sufficient to cover the paper substrate, and coating unevenness can be prevented. This improves air barrier properties. 2 By satisfying the above condition, the production cost of the laminate can be reduced, and the blocking property of the coating agent is also improved.
[0056] <Coating method> As a method for applying the coating liquid to the laminate, a conventionally known method can be used, but the flexographic method and the gravure method are preferred. The flexographic method is a method in which the coating agent is transferred from an intaglio plate called an anilox roll to a resin plate or a rubber plate, and the coating agent on the resin plate or the rubber plate is transferred to the original roll. It is also possible to pattern the resin plate or the rubber plate. The gravure method includes a method in which the coating agent is transferred directly from the intaglio plate to the original roll, and a so-called gravure offset method in which the coating agent is transferred from the intaglio plate to a flat plate and then transferred to the original roll. It is also possible to pattern the intaglio plate. In the case of the gravure method, it is preferable to perform a press treatment with a smoothing roll after coating. Of these methods, the flexographic method is more preferred. By using the flexographic method, it is easier to form a more uniform film on the paper substrate.
[0057] <Air shielding> In this application, air barrier is defined as a pressure reduction device that is used to reduce the air barrier effect by a diameter of 4 cm and an area of 12.56 cm. 2 The degree of vacuum was measured by placing a laminate in the opening under conditions where the hydraulic pump was set so that the degree of vacuum was 70 kPa when copy paper (product name: Multi Paper Super White+, manufactured by Askul Corporation) was placed in the opening. The smaller the value, the higher the degree of airtightness, meaning that a film is formed on the paper base material without any gaps.
[0058] The laminate of the present invention has an air barrier property of 20 kPa or less. More preferably, it is 10 kPa or less, and even more preferably, it is 5 kPa or less. The inventors have found that a laminate having an air barrier property of 20 kPa or less can retain the aroma components of food without letting them escape. This allows the deliciousness of the food to be felt more when eating it.
[0059] The air barrier property is measured using the device shown in Figure 1. A glass filter 2 is installed on the top of a glass container 1, and a rubber tube 3 is attached to the side of the glass container, to which a hydraulic pump 4 and a vacuum gauge 5 are connected. The hydraulic pump 4 is used to reduce the pressure, and the degree of reduction is measured using the vacuum gauge 5. Only the filter part 6 at the top of the device is designed to allow air to pass through, and the other parts are completely sealed. The filter part 6 is circular with a diameter of 4 cm, and the glass filter part is flat with respect to the glass part around the glass filter, and is neither protruding nor recessed. If the glass filter part is not flat, an accurate degree of reduction cannot be measured when the laminate is installed. The laminate 7 is installed on the glass filter part so that the coated surface faces down, and the degree of reduction is measured, and the value obtained is taken as the air barrier property. EXAMPLES
[0060] The present invention will be described in more detail below with reference to examples, but the following examples are not intended to limit the scope of the invention. In the examples, unless otherwise specified, "parts" means "parts by mass," "%" means "% by mass," the values in the tables are solid content masses, and blanks indicate that no space is used. The glass transition temperature and acid value of the polymer (A) are measured by the following methods.
[0061] <Glass transition temperature> The glass transition temperature of the polymer (A) was measured using a DSC (differential scanning calorimeter manufactured by TA Instruments). Specifically, an aluminum pan containing about 10 mg of the dried resin was weighed out and placed in it, and an empty aluminum pan as a reference was set in a DSC measurement holder, and the pan was rapidly cooled to -100°C in a nitrogen stream, and then heated to 200°C at 20°C / min to plot a DSC curve. The temperature at the intersection of the baseline on the low-temperature side of the endothermic phenomenon in this DSC curve and the tangent at the inflection point was taken as the glass transition temperature.
[0062] <Acid value> The acid value of the polymer (A) was calculated from the value obtained by potentiometric titration of 0.1 to 5 g of the resin previously dried according to the method described in JIS K2501:2003 (the amount of the sample was adjusted according to the acid value of the polymer (A)). Specifically, the sample was dissolved in a titration solvent containing toluene, 2-propanol, and a small amount of water, and potentiometric titration was performed with a 2-propanol solution of potassium hydroxide using a glass electrode and a reference electrode. The relationship between the pH meter reading and the corresponding titration amount of the 2-propanol solution of potassium hydroxide was plotted, and the inflection point obtained on the titration curve was taken as the end point. The acid value was calculated using the amount (mL) of the 2-propanol solution of potassium hydroxide used in the titration as described in "7.8.3 Calculation Method" of JIS K2501:2003.
[0063] The surfactants used in Table 1 were as follows: Emal 0: Manufactured by Kao Corporation, sodium lauryl sulfate, 100% active ingredient Perex OT-P: Kao Corporation, dioctyl sodium sulfosuccinate, active ingredient 70% Noigen TDS-120: Manufactured by Daiichi Kogyo Seiyaku Co., Ltd., polyoxyethylene tridodecyl ether, 100% active ingredient
[0064] <Synthesis of polymer (A1)> A reaction vessel (reaction tank) equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser was charged with 83.6 parts of water and 0.3 parts of EMALE 0 (100% active ingredient, sodium lauryl sulfate, manufactured by Kao Corporation). Separately, 30.0 parts of ethyl acrylate, 53.0 parts of methyl methacrylate, 7.0 parts of n-butyl methacrylate, 10.0 parts of methacrylic acid, 3.9 parts of t-dodecyl mercaptan, 0.80 parts of EMALE 0, and 52.9 parts of water were mixed and stirred in advance to prepare an emulsion of ethylenically unsaturated monomers (first-stage dropping tank) to be dropped into the first stage. The internal temperature of the reaction vessel was raised to 80°C and nitrogen substitution was sufficiently performed, and then 5.5 parts of a 5% aqueous solution of potassium persulfate was added as an initiator to start emulsion polymerization. While maintaining the internal temperature at 80°C, the emulsion of the ethylenically unsaturated monomer to be dropped in the first stage and 5.5 parts of a 5% aqueous solution of potassium persulfate were added dropwise over 2 hours. After the first stage ethylenically unsaturated monomer emulsion was dropped, 30 minutes later, ethyl acrylate 30.0 parts, methyl methacrylate 47.0 parts, n-butyl methacrylate 10.0 parts, n-butyl acrylate 23.0 parts, acrylic acid 2.0 parts, 2-ethylhexyl acrylate 15.0 parts, cyclohexyl methacrylate 2.0 parts, glycidyl methacrylate 1.0 parts, diethylene glycol dimethacrylate 1.0 parts, t-dodecyl mercaptan 0.1 parts, emal 0 1.20 parts, water 160.8 parts were mixed and stirred in advance to prepare the second stage ethylenically unsaturated monomer emulsion (second stage dropping tank) and 11.1 parts of a 10% aqueous solution of ammonium persulfate. After the dropwise addition was completed, the mixture was reacted at 80 ° C for another 3 hours. After the reaction was completed, 7.9 parts of 25% aqueous ammonia was added with stirring to neutralize. Then, water was further added to adjust the non-volatile content to 40.0%, and an aqueous dispersion of polymer (A1) was obtained. The Tg of polymer (A1) was 8.9°C and 52.2°C, and the acid value was 35.0mgKOH / g.
[0065] <Synthesis of polymers (A2) to (A11), (X1), and (X2)> In preparing polymer (A1), the components and amounts of the reaction tank, the first dropping tank, the second dropping tank, and the mass parts of 25% ammonia water were replaced as shown in Table 1, and aqueous dispersions of polymers (A2) to (A11), (X1), and (X2) were obtained in the same manner as for polymer (A1). For polymers (A4), (X1), and (X2), the amount of water charged in the second dropping tank was changed from 160.8 parts to 250.8 parts, and for polymers (A5), (A6), (A9), and (A10), it was changed to 130.8 parts. The acid value, high-temperature Tg, and low-temperature Tg of each polymer are shown in Table 1.
[0066] [Table 1]
[0067] <Synthesis of polymer (A12)> In a reaction vessel (reaction tank) equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser, 237.8 parts of water and 0.86 parts of PELLEX OT-P (Kao Corporation dioctyl sulfosuccinate sodium active ingredient 70%) were charged. Separately, 71 parts of methyl methacrylate, 16.5 parts of n-butyl acrylate, 12.5 parts of methacrylic acid, 3.0 parts of t-dodecyl mercaptan, 2.01 parts of PELLEX OT-P, and 65.8 parts of water were mixed and stirred in advance to prepare an emulsion of ethylenically unsaturated monomers (first-stage dropping tank) to be dropped into the first stage. The internal temperature of the reaction vessel was raised to 80°C and nitrogen replacement was sufficiently performed, and then 12.1 parts of a 5% aqueous solution of potassium persulfate was added as an initiator to start emulsion polymerization. While maintaining the internal temperature at 80°C, the emulsion of the ethylenically unsaturated monomer to be dropped in the first stage and 5.5 parts of a 5% aqueous solution of potassium persulfate were added dropwise over 2 hours. After completion of the dropping, the mixture was reacted for 2 hours, and neutralized by adding 9.9 parts of 25% aqueous ammonia while maintaining the temperature at 80°C. Next, a second stage ethylenically unsaturated monomer solution (second stage dropping tank) prepared by mixing 50.0 parts of methyl acrylate and 102.0 parts of n-butyl acrylate in advance and 24.2 parts of a 10% aqueous solution of ammonium persulfate were dropped over 2 hours. After completion of the dropping, the mixture was reacted for another 3 hours while maintaining the temperature at 80°C. Then, water was further added to adjust the non-volatile content to 40.0%, and an aqueous dispersion of polymer (A12) was obtained. The Tg of polymer (A12) was -10.8°C and 70.4°C, and the acid value was 32.3 mgKOH / g.
[0068] <Synthesis of polymers (A13) to (A16) and (X3)> In preparing polymer (A12), the components and amounts of the reaction tank, the first dropping tank, and the second dropping tank, and the parts by mass of 25% ammonia water were replaced as shown in Table 1, and aqueous dispersions of polymers (A13) to (A16) and (X3) were obtained in the same manner as for polymer (A12). The acid value, high-temperature Tg and low-temperature Tg of each polymer are shown in Table 1.
[0069] [Manufacturing Examples 1-16] Water was added to the polymer (A1) solution so that the nonvolatile content was 38%, to prepare coating liquid 1. Similarly, water was added to the polymers (A2) to (A16) solutions so that the nonvolatile content was 38%, to prepare coating liquids 2 to 16.
[0070] [Examples 17-37] Polymer (A2), (A12), (A14) solution, wax, and antifoaming agent were mixed so that the mass ratio of the nonvolatile content of each was as shown in Table 2, and after stirring uniformly with a disper, water was added so that the nonvolatile content of the coating liquid was 38%. Coating liquids 17 to 37 were prepared.
[0071] [Examples 38-40] Coating Liquids 38 to 40 were obtained in the same manner as in Production Example 1, except that the polymer (A1) solution was replaced with the polymer (X1) to (X3) solutions.
[0072] [Table 2]
[0073] The waxes and defoamers shown in Table 2 were as follows: Paraffin wax 1: Dispersion of paraffin wax with a melting point of 60°C in water (non-volatile content 30%) Paraffin wax 2: Dispersion of denatured paraffin with a melting point of 90°C in water (non-volatile content 30%) Polyethylene wax 1: Water dispersion of polyethylene with a melting point of 125°C and a non-volatile content of 30% Polyethylene wax 2: Water dispersion of polyethylene with a melting point of 110°C and a non-volatile content of 30% Emulsion-type silicone defoamer 1: An emulsion containing 20% polysiloxane (oil type) and 2% surfactant, with a non-volatile content of 22%. Compound type silicone-based defoamer 2: A compound type silicone-based defoamer containing polysiloxane (oil type) and fumed silica, with a non-volatile content of 100%.
[0074] <Preparation of Laminate> [Example 1] Coating liquid 1 was applied to the glossy side of commercially available sanitary paper (weighing 21 g, gloss-treated on one side) at a coating speed of 150 m / min using a Windmiller & Hoelscher "SOLOFLEX" central impression (CI) type six-color flexographic printing press. Two separate units, each with a capacity of 7 cc, were used to coat the glossy side twice. The product was then dried in an oven at 80°C to obtain laminate 1. The coating amount of the coating layer (L) in laminate 1 was measured and found to be 2 g / m 2 It was.
[0075] [Examples 2 to 16] Laminates 2 to 16 were produced in the same manner as in Example 1, except that Coating Liquid 1 was changed to Coating Liquids 2 to 16.
[0076] [Examples 17 to 22] Laminates 17 to 22 were produced in the same manner as in Example 1, except that Coating Liquid 8 was used instead of Coating Liquid 1 and the capacity of the anilox roll was changed to the coating amount of the coating layer (L) as shown in Table 3.
[0077] [Examples 23 to 43] Laminates 23 to 43 were produced in the same manner as in Example 1, except that the coating liquid 1 was changed to coating liquids 17 to 37.
[0078] [Comparative Examples 1 to 3] Laminates 44 to 46 were produced in the same manner as in Example 1, except that Coating Liquid 1 in Example 1 was changed to Coating Liquids 38 to 40.
[0079] [Comparative Examples 4 and 5] Laminates 47 and 48 were prepared in the same manner as in Example 1, except that coating liquid 8 was used instead of coating liquid 1 in Example 1 and the capacity of the anilox roll was changed to the coating amount of the coating layer (L) as shown in Table 5.
[0080] Evaluation items and evaluation methods The evaluation items and evaluation methods for the laminate are as follows. The evaluation results are shown in Tables 3 to 5.
[0081] <Oil resistance test> A drop of castor oil was dropped onto the coating layer (L) of the obtained laminate in an environment of 23°C, and after 30 seconds, it was confirmed whether the castor oil had soaked into the laminate. Evaluation was made based on the percentage of the area onto which the castor oil had soaked and discolored the paper. [Evaluation Criteria] 5: No penetration at all (very good) 4: Less than 10% of the surface area is saturated (good) 3: The area soaked is between 10% and 30% (fairly good) 2: The area soaked is between 30% and 50% (usable) 1: More than 50% of the surface area is saturated (very poor)
[0082] <Blocking resistance test> The surface of the coating layer (L) of the obtained laminate was placed on the surface of a paper substrate in an environment of 23° C., and the blocking resistance was evaluated using the following device and conditions. Equipment: CO-201 permanent deformation tester (manufactured by Tester Sangyo Co., Ltd., upper and lower plate heating) Pressure: 2kg / cm 2 Temperature: 40℃ Hours: 24 hours [Evaluation Criteria] 5: There is absolutely no resistance when peeling off, and the glossy paper is not damaged on one side (very good) 4: There is almost no resistance when peeling off, and one side of the glossy paper is not damaged (good) 3: There is some resistance when peeling, but one side of the glossy paper is not damaged (fairly good) 2: There is some resistance when peeling off, but the glossy paper is not damaged (usable) 1: There is resistance when peeling off, and one side of the glossy paper is missing (unusable)
[0083] <Heat sealability> The obtained laminate was cut into a width of 15 mm, and the heat seal strength was measured using the test pieces as follows, using the following equipment and under the following conditions. (Heat seal) Equipment: HEATSHEEL & IMPULSE TESTER (manufactured by Nichiri Kagaku Kogyo Co., Ltd., upper and lower plate heating) Temperature: 130℃ Pressure: 2kgf / cm 2 Time: 1 second (peel off) Equipment: Tensile testing machine (manufactured by Tester Sangyo Co., Ltd.) Peeling conditions: 180° peeling, 300mm / min [Evaluation Criteria] 5: 2.5N or more (very good) 4: 2N or more, less than 2.5N (good) 3: 1.5N or more, less than 2N (fairly good) 2: 1N or more, less than 1.5N (usable) Less than 1:1N (unusable)
[0084] <Seasoning resistance test> In an environment of 23°C, a drop of a mixture of ketchup / vinegar / salad oil = 1 / 1 / 1 (mass ratio) was dropped onto the coating layer (L) of the obtained laminate, and the time it took for the drop on the surface to pass through one side of the glossy paper and reach the back side was measured. [Evaluation Criteria] 5: 90 minutes or more (very good) 4: 70 minutes or more, less than 90 minutes (good) 3: 50 minutes or more, less than 70 minutes (fairly good) 2: 30 minutes or more, less than 50 minutes (usable) Less than 1:30 minutes (unavailable)
[0085] <Microwave resistance test> A piece of "Tokukara Fried Chicken" manufactured by Nichirei Foods, Inc. was placed on the coating layer (L) of the laminate and heated in a microwave oven at 500W for 180 seconds, then left to stand for 20 minutes to return to room temperature. The piece of fried chicken was then removed and the state of penetration of oil and moisture into the sheet surface and the presence or absence of the fried chicken sticking to the sheet (blocking between the food and the sheet) were checked. [Evaluation Criteria] 5: Oil and moisture do not penetrate the sheet, and the fried chicken does not stick to the sheet. (Very good) 4: There is some oil and water penetration, but it does not penetrate to the back side, and the fried chicken does not stick to the sheet. (Good) 3: Oil and water have penetrated, but not to the back side, and the fried chicken does not stick to the sheet. (Fairly good) 2: Oil and water have penetrated, but not to the back side. The fried chicken is slightly sticking to the sheet (less than 10% of the contact area). (Can be used) 1: Oil or moisture has penetrated to the back side, or the fried chicken is stuck to the sheet (more than 10% of the sheet contact area). (Not for use)
[0086] <Water resistance> A drop of water was dropped onto the coating layer (L) of the obtained laminate in an environment of 23°C, and after 30 seconds, it was confirmed whether the water had soaked into the laminate 1. Evaluation was made based on the percentage of the area onto which the water had soaked and the color of the paper had changed. [Evaluation Criteria] 5: No penetration at all (very good) 4: Less than 10% of the surface area is saturated (good) 3: The area soaked is between 10% and 30% (fairly good) 2: The area soaked is between 30% and 50% (usable) 1: More than 50% of the surface area is saturated (very poor)
[0087] <Air shielding> The air barrier property in this specification was measured by the method described in the section on air barrier property above. The obtained laminate was cut into a size of 5 cm x 5 cm, and the laminate was placed while reducing the pressure so that the coated surface was aligned with the glass filter surface. At this time, the laminate and the glass filter surface were completely attached to each other so that the laminate would not bend and wrinkle. After placing the laminate at the measurement location, the vacuum level was read after the vacuum gauge reading stabilized, and this was taken as the air barrier value. The measurement was carried out in a constant temperature and humidity room at a temperature of 25°C and a humidity of 60%. The obtained values were evaluated as follows. [Evaluation Criteria] 5: Air barrier value is 2kPa or less (very good) 4: Air barrier value is greater than 2kPa and less than 5kPa (good) 3: Air barrier value is greater than 5kPa and less than 10kPa (fairly good) 2: Air barrier value is greater than 10kPa and less than 20kPa (usable) 1: Air barrier value is greater than 20 kPa (very poor)
[0088] [Table 3]
[0089] [Table 4]
[0090] [Table 5]
[0091] [Examples 44 to 52, Comparative Examples 6 to 8] <Food flavor retention> Laminates 1, 3, 4, and 38 to 46 were cut into 30 cm x 30 cm pieces, and a piece of "Original Chicken" manufactured by KFC Japan, which had been heated to 50°C, was placed in the center of the piece, which was then wrapped from all sides to ensure there were no gaps, and left for 20 minutes in an environment at 23°C. After that, 10 subjects opened the packaging, ate the contents, and compared it with the unwrapped piece left for 20 minutes at 23°C (control), and scored as follows: 3 points: The flavor was stronger than normal. 2 points: The flavor was slightly stronger than normal. 1 point: Flavor was felt to be about the same as standard. The average scores of the 10 subjects were judged according to the following criteria, and designated Examples 44 to 52 and Comparative Examples 6 to 8. The results are shown in Table 6. ◎: Average value is 2.5 points or more (good) ○: Average value is 1.5 points or more and less than 2.5 points (usable) ×: Average value is less than 1.5 points (extremely poor)
[0092] [Table 6] [Explanation of symbols]
[0093] 1 glass container 2 Glass Filter 3 Rubber tube 4 Hydraulic pump 5 Vacuum gauge 6 Filter section 7 Laminate (measurement sample)
Claims
1. A coating layer (L) is provided on at least one surface of the paper substrate, The coating layer (L) contains a polymer (A) made of an ethylenically unsaturated monomer (a), The polymer (A) has a glass transition temperature in the range of −40 to 30° C. and a glass transition temperature in the range of 40 to 140° C., and the acid value is 20 to 40 mgKOH / g; The coating amount of the coating layer (L) is 0.5 to 10 g / m 2 And A laminate having an air barrier property of 20 kPa or less.
2. 2. The laminate according to claim 1, wherein the ethylenically unsaturated monomer (a) contains an alkyl (meth)acrylate (a-1) in which the alkyl group is a methyl group, an ethyl group, or an alkyl group having 3 to 8 carbon atoms.
3. 3. The laminate according to claim 1, wherein the ethylenically unsaturated monomer (a) contains 85 to 97 mass% of alkyl (meth)acrylate (a-1-1) in which the alkyl group is a methyl group, an ethyl group, or a linear alkyl group having 3 to 4 carbon atoms, based on the total mass of the ethylenically unsaturated monomer (a).
Citation Information
Patent Citations
Oilproof paper for food
JP2001303475A
Gas-barrier laminate
JP2005271467A
Packaging material, and paper container
JP2011235926A
Coating agent for food packaging paper and coated paper for packing food
JP2013241716A
Food packaging paper and food packaging method using the same
JP2021038022A